POTENSI PENYALAHGUNAAN KEWENANGAN OLEH PEJABAT ADMINISTRASI NEGARA DALAM PENGAMBILAN DAN PELAKSANAAN KEBIJAKAN PUBLIK - Charda S., Ujang (Sekolah Tinggi Hukum Bandung, 2012)
The potential abuse of power that motivated malicious intent would be to have the perfection that is attached to the power, because the positions of power can do anything with a plea for and on behalf of its authority under the legislation. Therefore, the act of state administration in upholding the rule of law requires for its implementation, otherwise the power itself is determined by the legal limits. To that end, the law and the power of an absolute element in a society of law in the sense of community that is governed by law and that any act or authority is not misused.Keywords : legitimasi â administrasi negara â kebijakan public